Ammonothermal Synthesis of Alkali‐Alkaline Earth Metal and Alkali‐Rare Earth Metal Carbodiimides: K5–xMx(CN2)2+x(HCN2)1–x (M = Sr, Eu) and Na4.32Sr0.68(CN2)2.68(HCN2)0.32. Issue 23 (16th October 2017) - Mallmann, Mathias; Häusler, Jonas; Cordes, Niklas; Schnick, Wolfgang
Abstract : Alkali‐alkaline earth metal and alkali‐rare earth metal carbodiimides, namely K5– x Mx (CN2 )2+ x (HCN2 )1– x ( x = 0 – 1) ( M = Sr, Eu) and Na4.32 Sr0.68 (CN2 )2.68 (HCN2 )0.32, were synthesized under ammonothermal conditions in high‐pressure autoclaves. The structures of the three compounds can be derived from homeotypic K5 H(CN2 )3 and Na5 H(CN2 )3 by partial substitution of K + or Na + by Sr 2+ or Eu 2+ . The reactions were carried out in two step syntheses ( T 1 = 673 K, T 2 = 823 K) starting from sodium or potassium azide, dicyandiamide and strontium or Eu(NH2 )2, respectively. The crystal structures were solved and refined from single‐crystal X‐ray diffraction data [K4.16 Sr0.84 (CN2 )2.84 (HCN2 )0.16 : space group Im 3 m (no. 229), a = 7.8304(5) Å, Z = 2, R 1 = 0.024, wR 2 = 0.052; K4.40 Eu0.60 (CN2 )2.60 (HCN2 )0.40 : space group Im 3 m (no. 229), a = 7.8502(6) Å, Z = 2, R 1 = 0.022, wR 2 = 0.049]. In contrast to the potassium carbodiimides, the sodium‐strontium carbodiimide was only synthesized as microcrystalline powder. The crystal structure was determined by powder X‐ray diffraction and refined by the Rietveld method [Na4.32 Sr0.68 (CN2 )2.68 (HCN2 )0.32 : space group Im 3 m (no. 229), a = 7.2412(1) Å, Z = 2, R wp = 0.050]. The presence of hydrogencyanamide units ([HNCN] – ) next to carbodiimide units ([CN2 ] 2– ) in all compounds was confirmed by FT‐IR spectroscopy. Abstract :